PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KARTU PENGPAS (PENGETAHUAN IPAS) UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPAS KELAS IV SD - Dameria, Avila; Kristin, Firosalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to develop learning media based on the PengPAS Card (Science and Technology Knowledge) in order to increase the motivation and learning outcomes of science science in Grade IV of elementary school. This research uses the Research and Development (R&D) method, with the stages of product analysis, development, and testing effectiveness. Data was collected through interviews with grade IV teachers, observations, and expert validation. The validity of the PengPAS card media obtained a score of 95%, with the category of very good, and validation by material experts obtained a score of 93%. The practicality of the media is also considered very good with 95% of the students' responses. The learning motivation of students increased significantly, from 33% or 8 students who had very low motivation and 65% with a total of 16 students in the low category, to 83% very high with the number of 20 students and 17% high with the number of students 4, after using the PengPAS card. The results of the independent samples test showed a significance of 0.000 < 0.005, with an average score of 60.42 and a postest score of 90.04, indicating a significant improvement in learning outcomes. In conclusion, the PengPAS card media is effective in increasing the motivation and learning outcomes of science science in grade IV elementary school.